Green Sponsorship in Global Sports: Between Corporate Branding and Authentic Environmental Action: A Literature Review - Lea, Felisa Romo; Barton, Gertude; Mayr, Alexander (Global Insights in Management and Economic Research, 2025)
Purpose of the study: This systematic literature review investigates green sponsorship in global sports, focusing on the interplay between corporate environmental branding and genuine sustainability initiatives, while analyzing the effectiveness of environmental sponsorship practices and their impact on corporate reputation and environmental outcomes. Materials and methods: A systematic literature review was conducted using various electronic databases, covering publications from 2010 to 2024, with specific search terms and inclusion criteria resulting in 67 relevant studies after screening 847 initial articles. Results: The analysis identified three categories of green sponsorship: (1) Authentic environmental partnerships (23%), (2) Strategic green branding (54%), and (3) Superficial greenwashing (23%), with findings showing that authentic partnerships yield significantly higher brand loyalty compared to greenwashing. Conclusions: Green sponsorship ranges from genuine commitment to superficial tactics; authentic partnerships positively affect corporate reputation and environmental outcomes, whereas greenwashing erodes consumer trust, necessitating future research on metrics for evaluating authenticity and impact.